KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN SUMBER DAYA ALAM (Tinjauan Yuridis Kekhususan Suatu Daerah Dalam Sistem Negara Kesatuan Republik Indonesia) - Dwi Kherisna Payadnya; I Wayan Suarbha (Kertha Negara : Journal Ilmu Hukum, 2014)
This paper shall be entitled as Local Government Authority in NaturalResources Management (Juridical Approach of Regional Specifity within Republic ofIndonesia).By applying normative legal research method, this writing shall describe theauthority of local authority in managing natural resources. As stipulated in 1945Constitution, Article 18 (2), (5) and (6), Article 18A (1) along with its operatinglegislation, namely Law No. 32 of 2004, Law No. 21 of 2001 based on considerations c,f, g, h, i and article 34 , and Law No. 33 of 2004 article 11 point (1) and (3), article 19point (1) and (2). Within this matter, local government shall possesses the authority inmanaging the natural resources upon the basis of decentralizing principle, pursuant toArticle 17 point (1) of Law No. 32 of 2004.